Patterns and root causes of exposure to ergonomics risk factors among Malaysian office workers: retrospective study from practitioners’ reports - Radin Umar, Radin Zaid; Nazihah Mohamad,; Tiong, Jing Yin; Ahmad, Nadiah (International Journal of Occupational Safety and Health, 2025)
Introduction: Symptoms of musculoskeletal disorders are common among office workers worldwide. However, there has been limited published data that examine patterns and root causes of exposures to ergonomics risk factors, especially sourced from ergonomists’ assessment reports. This study investigates the prevalence rates of musculoskeletal disorder (MSD) symptoms, ergonomics risk factor exposure patterns, and root causes of these exposures among office workers in Malaysia from ergonomists’ perspectives.Methods: A retrospective study was conducted among Malaysian office workers. Data were extracted from 399 individual ergonomics assessment reports prepared by professional ergonomists. These reports were obtained over a period of 17 years (March 2001 until November 2018), across 16 different offices in 5 states and 1 federal territory. In addition to self-reported body symptom data, extracted data includes ergonomics risk factors and root causes identified by professional ergonomists. Descriptive and statistical analyses were conducted to determine patterns from extracted data.Results: Data showed high MSD symptoms prevalence (87%) of varying degrees among the sample population. The body parts most affected among sample population include shoulder (42%), lower back (38%), and neck (32%). Gender and age are seen to be associated with the reported MSD symptoms severity levels. Common ergonomic risk factors among office workers include poor posture (97%), static loading (90%), and contact stress (74%). The majority of the root causes of an individual’s ergonomic exposures can be traced to substandard workstation setups as well as poor work habits.Conclusion: The study provides insight into patterns and root causes of exposure to ergonomics risk factors among Malaysian office workers from an ergonomist’s point of view.